SURGICAL DISLOCATION OF THE HIP IN PATIENTS WITH FEMOROACETABULAR IMPINGEMENT. SURGICAL TECHNIQUES AND OUR EXPERIENCE - Mladenovic, Desimir (Vojnosanitetski pregled, 2015)
Introduction: We report our experience in the application of a safe surgical dislocation of the hip in patients with minor morphological changes in the hip joint, which, through the mechanism of femoroacetabular impingement, cause damage to the acetabular  labrum and adjacent cartilage as an early sign of the hip arthrosis.Materials and methods: We have operated 51 patients with different morphological bone changes in the hip area and resultant soft tissue damage of the acetabular labrum and its adjacent cartilage. Surgical technique that we applied in this group of patients, was adapted to our needs and capabilities and it was minimaly modified compared to the original procedure.Conclusion: The surgical technique presented in this paper, proved to be a good method of treatment of bone and soft tissue pathomorphological changes of the hip in patients with femoroacetabular impingement. We had no cases of  patients with avascular necrosis of the femoral head, and two patients had nonunion of the greater trochanter, 9 patients developed paraarticular ossification, without subjective symptoms, while 3 patients suffered from postoperative pain in the groin during more energetic physical activities.Key words: surgical technique, femoroacetabular impingement, experience